Federalism as a Principle – Constitutional Consequences - Krunková, Alena (Federalism as the Future of the Diverse EU?, 2025)
The aim of this section is to examine federalism from the position of constitutional law and state science. Modern groupings of states are currently pushing the boundaries of traditional statehood in a new direction. This trend reveals new connections with open questions of state law. At the same time, it brings new challenges, the mastery of which presupposes a knowledge of the theoretical contexts and factual pitfalls of the application of federalism. The introduction is therefore essential to define the basic theoretical correlations of federalism as a principle of constitutionalism in relation to the territorial organisation of the state and the form of government. The form of government in the state is largely determined by the structure of its supreme bodies and the mutual relations between them. In addition, by their decisions, federal authorities determine the legal and factual level of relations between federation and member state. In the above context, it is necessary to examine the structure and relations of the main EU decision-making bodies, especially in view of possible federalist tendencies in the European Union.Keywords: Federalism, Constitutional Law, European Union, Composite states, Unitary states.